2015
DOI: 10.1152/ajpheart.00408.2015
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress upregulates placental growth factor in the vessel wall via NADPH oxidase 4

Abstract: Rashdan NA, Lloyd PG. Fluid shear stress upregulates placental growth factor in the vessel wall via NADPH oxidase 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 62 publications
4
22
0
Order By: Relevance
“…In several studies, areas of low WSS were proved to be found in areas of turbulence, and these sites are correlated with those prone to atherosclerotic plaque development. 21,22 The general patterns of WSS reported in our research corresponded well with the available data. However, inside the big vortex for severely deformed vessels, higher velocity and heterogeneity usually appear, resulting in higher WSS and WP, due to the striking of the flow.…”
Section: Discussionsupporting
confidence: 89%
“…In several studies, areas of low WSS were proved to be found in areas of turbulence, and these sites are correlated with those prone to atherosclerotic plaque development. 21,22 The general patterns of WSS reported in our research corresponded well with the available data. However, inside the big vortex for severely deformed vessels, higher velocity and heterogeneity usually appear, resulting in higher WSS and WP, due to the striking of the flow.…”
Section: Discussionsupporting
confidence: 89%
“…For the Nox enzymes, however, we saw a remarkably similar pattern of expression across multiple cell isolates. Nox4 is also the predominant Nox enzyme expressed in other human vascular endothelial populations, including aortic, pulmonary arterial, umbilical venous and coronary arterial endothelial cells …”
Section: Discussionmentioning
confidence: 99%
“…Nox4 is also the predominant Nox enzyme expressed in other human vascular endothelial populations, including aortic, pulmonary arterial, umbilical venous and coronary arterial endothelial cells. [28][29][30][31] As was comprehensively summarized in the recent review by Wang and Hartnett,32 Nox4 participates in endothelial homeostatic and pathological processes; the nature of this involvement relates to multiple variables that include tissue location and timing, as well as the process in question. Thus, in comparison to control animals, Nox4 gene-deleted mice or mice treated with Nox4 inhibitor demonstrate reduced capillary growth in the gastrocnemius muscle, in response to running exercise on a wheel or treadmill 33 ; poor recovery of capillary density and blood flow in the leg following femoral artery ligation 34 ; and less aggressive pulmonary neovascularization in experimental pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin binding EGF-like growth factor is one such factor which is expressed in response to reduced blood flow and induces vessel narrowing [95]. Other molecular pathways involved in vascular remodelling are reported to be regulated by changes in shear stress leading to the expression of PlGF [96], Notch-1 [97], and Smad6 (involved in TGB-β signalling) proteins [98].…”
Section: Haemodynamic Factorsmentioning
confidence: 99%